The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2967/jnumed.119.229740
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Assessment of 18F-(2S,4R)-4-Fluoroglutamine in Patients with Cancer

Abstract: 18 F-(2S,4R)-4-fluoroglutamine (18 F-FGln) is an investigational PET radiotracer for imaging tumor glutamine flux and metabolism. The aim of this study was to investigate its pharmacokinetic properties in patients with cancer. Methods: Fifty lesions from 41 patients (21 men and 20 women, aged 54 ± 14 y) were analyzed. Thirty-minute dynamic PET scans were performed concurrently with a rapid intravenous bolus injection of 232 ± 82 MBq of 18 F-FGln, followed by 2 static PET scans at 97 ± 14 and 190 ± 12 min after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…18 F-Gln-PET has been explored as a measure of glutamine metabolism in early clinical trials. 18 F-Gln uptake was seen in a variety of cancers: paraganglioma, breast, colon, lung, pancreas, neuroendocrine, glioma, and thyroid (16)(17)(18)(19)35). Down sloping TACs in these human tumors support reversible kinetics.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…18 F-Gln-PET has been explored as a measure of glutamine metabolism in early clinical trials. 18 F-Gln uptake was seen in a variety of cancers: paraganglioma, breast, colon, lung, pancreas, neuroendocrine, glioma, and thyroid (16)(17)(18)(19)35). Down sloping TACs in these human tumors support reversible kinetics.…”
Section: Discussionmentioning
confidence: 93%
“…18 F-Glutamate (8-9% of total activity) was seen in the supernatant of mice and rat tumor extracts on HPLC analysis at one hour (20). We note that there has been an alternative compartment model proposed for 18 F-Gln that hypothesize significant metabolism of 18 F-Gln to 18 F-Glutamate (19). Our prior studies in breast cancer mouse models demonstrated that ≥85% of the radioactivity in the supernatant of tumor tissue was in the form of 18 F-Gln and only 9-14% of activity was from metabolites (12).…”
Section: Compartmental Modelmentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, it was shown that CB-839 and Sapanisertib (TAK-228), inhibitor of mTORC1/2, therapies decreased the rate of glutaminolysis. Therefore, 18 F-FGln dynamic PET allows for the study of glutamine flux in patients with cancer, which necessary in order to evaluate specific cancer types with glutamine addiction, as well as responses to targeted therapies with inhibitors of the glutaminolysis pathway [67].…”
Section: Therapeutic Approaches Targeting the Glutaminolysis Pathway mentioning
confidence: 99%
“…F-Gln uptake has been shown to be enhanced in glutamine-avid tumors. 13 Total-body dynamic PET imaging 14 will enable fully quantitative analysis of glucose utilization (for 18 F-FDG) and glutamine transport and conversion to glutamate (for 18 F-Gln) for all lesions.…”
mentioning
confidence: 99%